2016
DOI: 10.1093/femsec/fiw198
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-cycling process rates across urban ecosystems

Abstract: Nitrogen (N) pollution of freshwater, estuarine, and marine ecosystems is widespread and has numerous environmental and economic impacts. A portion of this excess N comes from urban watersheds comprised of natural and engineered ecosystems which can alter downstream N export. Studies of urban N cycling have focused on either specific ecosystems or on watershed-scale mass balances. Comparisons of specific N transformations across ecosystems are required to contextualize rates from individual studies. Here we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
45
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 90 publications
4
45
1
Order By: Relevance
“…A review of N cycling across urban ecosystems found that various N spiraling metrics, which quantify different aspects of N cycling within streams (Stream Solute Workshop ), were as high or higher in urban streams compared to reference streams (Reisinger et al. ). This result shows that in spite of multiple stressors associated with the urban stream syndrome, urban streams remain capable of high rates of N uptake and removal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of N cycling across urban ecosystems found that various N spiraling metrics, which quantify different aspects of N cycling within streams (Stream Solute Workshop ), were as high or higher in urban streams compared to reference streams (Reisinger et al. ). This result shows that in spite of multiple stressors associated with the urban stream syndrome, urban streams remain capable of high rates of N uptake and removal.…”
Section: Introductionmentioning
confidence: 99%
“…Despite multiple physical, chemical, and biological stressors (Walsh et al 2005, Wenger et al 2009), urban streams remain capable of providing high rates of various ecosystem functions, even in unrestored states (Reisinger et al 2016). Nitrogen (N) cycling, in particular, represents a critical function of stream ecosystems across a range of human land uses (Mulholland et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a recent review found that stream nitrogen uptake rates were similar between reference and urban streams across a range of urban settings (Reisinger et al. ), and urban stream networks are dynamic transformers of materials and energy, particularly during baseflow (Kaushal et al. , b).…”
Section: Introductionmentioning
confidence: 99%
“…These physicochemical and biological changes to urban streams are speculated to result in reductions in stream ecosystem functions such as metabolism and nutrient uptake, despite a limited amount of empirical evidence (Walsh et al 2005, Wenger et al 2009). In fact, a recent review found that stream nitrogen uptake rates were similar between reference and urban streams across a range of urban settings (Reisinger et al 2016), and urban stream networks are dynamic transformers of materials and energy, particularly during baseflow (Kaushal et al 2014a, b).…”
Section: Introductionmentioning
confidence: 99%